The Routledge handbook of European public policy - Zahariadis, Nikolaos; Buonanno, Laurie (Routledge, 2018)
EU policymaking : issues and debates / Laurie Buonanno and Nikolaos Zahariadis -- Principal-agent models / Yannis Karagiannis and Mattia Guidi -- Regulatory governance in the EU / Alessandro Cagossi -- Multiple streams / Nicole Herwig and Nikolaos Zahariadis -- Punctuated equilibrium theory / Christian Breunig, Daniela Beyer, and Marco Radojevic -- The internal market / Laurie Buonanno -- EU competition rules and the European integration project / Angela Wigge and Hubert Buch-Hansen -- Changing governance of cohesion policy / Carolyn Dudek -- Social policy / Claire Dupuy and Sophie Jacquot -- Gender policy / Sophie Jacquot -- Economic and monetary union / Waltraud Shelke -- Banking policy / Stefaan DeRynck -- The globalization trilemma and the EMU's second-order democratic deficit / Nikitas Konstantinidis and Ruben Treurniet -- The EU budget / Gabriele Cipriani -- European immigration and asylum policy / Alexander Caviedes -- Police and judicial cooperation policy / Stephen Rozee, Christian Kaunert and Sarah Leonard -- European Union privacy and data protection policy / George Christou -- The common foreign and security policy / Sara Kahn-Nisser -- Trade policy / Holly Jarman -- Enlargement policy / Neill Nugent -- The European neighbourhood policy / Mariam Dekanozishvili -- The cap : common dynamics of policy change in an uncommon policy domain / Gerry Alons and Pieter Zwaan -- European energy policy / Nicole Herwig -- EU policy on the environment / Jale Tosun -- Lobbying and interest group politics in the European Union / Andreas Hofmann -- Agenda setting in the European Union / Petya Alexandrova and Marcello Carammia -- Understanding the EU's policymaking institutions / John McCormick -- Strategic framing and the European Commission / Mark Rhinard -- Implementation and enforcement of EU polices / Gerda Falkner -- If evaluation is the solution, what is the problem? / Claire A. Dunlop and Claudio M. Radaelli -- Resisting in times of crisis : the implementation of European austerity plans in Ireland and Greece / Clement Fontan, Sabine Saurugger and Nikolaos Zahariadis -- Resistance in European Union health care policy / Scott L. Greer -- Evasion as a mechanism of resistance (not only) to European law / Annette Elisabeth Toller -- European level policy dynamics in higher education / Martina Vukasovic -- The infusion of Europe in public policy : the case of higher education / Pauline Ravinet
Includes bibliographical references and index
Keywords: European Union; European Union countries -- Economic policy; European Union countries -- Social policy; Electronic books; Staatstätigkeit; Europäische Union